Kahoot! App: An Interactive Tool to Enhance the English Participation of Grade 7 Students (American Journal of Arts and Human Science, 2022)
This study is aimed at improving the participation of 30 Grade 7 students during the Academic Year 2021-2022 through the Kahoot! App. Kahoot! is a game-based student-response system that focuses on engaging the students in the classroom. Through class observations and interviews, it was found that students were rarely volunteering to answer questions and contribute to the discussion because of the traditional tools used by the teacher. To further validate the researchers’ observations, the respondents were given a pre-survey checklist as well as a post- post-survey checklist. This was to determine their extent of participation before and after the employment of the intervention. Results showed that the mean score of the respondents in their pre-survey was 1.79 or Strongly Disagree, while in their post-survey, it was 4.41 or Strongly Agree which means that there was a mean difference of 2.63. Also, the t-value of -37.51 means that the pre-survey checklist obtained a lower result than the post-survey checklist. This is attributed to the fact that the students favored and preferred Kahoot! App than Google Form. In addition, the p-value of 0.000 is less than the .01 level of significance which further validates that there is a significant difference of the pre-survey and the post-survey. This implies that the intervention of this research proved to improve the participation of the students in English. Thus, the intervention of this study is highly recommended for teachers to use in facilitating assessment activities in online setting because of the its engaging features like colorful backgrounds, pictures, interesting graphics, and immediate feedback, which motivate the students to participate.